Agricultural intensification and livelihood strategies of female farmers in Babati District, Tanzania: A minor field study - Bengtsson, M.; Klerfelt, M. (University of Gothenburg, 2014)
In many parts of the world and especially in Sub-Saharan Africa and Tanzania, where the majority of the poorest people live, agriculture is the way to make a living. Life in agriculture is in many ways marked by gender inequality. Female farmers carry a heavy burden both in the farm activities and the household chores while at the same time lacking access to resources as well as power within and outside the household. This gendered disadvantage is changing over time and space although the structure of this disadvantage remains in all places of the world. In recent years the development agenda started focusing on agriculture to reduce poverty. The World Bank started promoting market-orientation for small-scale farmers, privatisation in land and agricultural intensification. Agricultural intensification is a concept to increase agricultural productivity by using more inputs for example labour, time or fertilisers. One place where agricultural intensification is an on-going process is in Babati District, Tanzania. Babati District was once characterised by fertile soils and available land and many people moved there to farm and the population increased. Today land scarcity and soil infertility are problems. Agricultural intensification is suggested as a solution. But with the prevailing structures of disadvantages in the livelihood opportunities for women we find it important to study how agricultural intensification affects the livelihoods of female farmers. The aim of this thesis is to identify and analyse the livelihood strategies of female farmers in relation to the process of agricultural intensification in six villages in Babati District. To find characterisations of the livelihood strategies of female farmers, the structure of livelihood strategies in general in the villages will also be studied and analysed. To reach the aim of the thesis three research questions are set up: • Which are the main livelihood strategies in the six villages? • What characterises the livelihood strategies of female farmers in the six villages? • How can the process of agricultural intensification affect the livelihood strategies of female farmers in the six villages? In order to answer the research questions we use qualitative methods consisting of seven focus group interviews with village officers and one Women’s Group and 15 semi-structured interviews with individual female farmers complemented by direct observations. The theoretical framework link agricultural intensification to the perspectives modernisation theory, the livelihood framework and the term gender is followed by previous research on development in agriculture, livelihoods and women in Sub-Saharan African agriculture. Our empirical findings show that agriculture is the main way to make a living for rural farmers where subsistence farming is the major livelihood strategy in all of the six villages. Other livelihood strategies constitute a part the socio-economically poorest households. Labour-oriented livelihood strategies specifically labourers working in the fields of other farmers struggle much to support their households. The diversification of livelihood strategies takes place in farming activities but not in non-farm activities. The livelihood strategies of female farmers are characterised by household chores and farming activities while lacking access to resources, capital, services and information. The process of agricultural intensification takes place in a context where the female farmers have a marginalised position.